Characterization of virgin coconut oil and multiple instrument approach for the detection of lard adulteration in model virgin coconut oil - Tengku Mansor, Tengku Salwani (2011)
The driving force for adulteration is to cut cost and to increase profit. However, in the case of adulteration using animal oils, this would also affect in terms of consumers beliefs and practice such as for Hindus, vegans and vegetarians, Jews and Muslims. For Muslims, adulteration using lard (LD) or improperly slaughtered animal oils is of significant issue. Detecting adulteration in fats and oils especially the high-value oils such as virgin coconut oil (VCO) is indeed needed. The attempt to find the most effective, simple, chemical-free and straightforward analysis without compromising the sensitivity and specificity is essential. Therefore, the overall objective of this study is to apply these three nstruments, namely differential scanning calorimeter (DSC), electronic nose/ fast gas-chromatography (fast GC) and Fourier transform infrared (FTIR) spectroscopy to detect LD adulterations in VCO. VCO is prepared through the ‘wet’ and ‘dry’ methods, while LD was rendered from adipose tissue of pig using microwave oven. In the first phase, the VCO samples were characterized and analyzed physicochemically. The results showed that in general all VCO samples conformed to the Asian and Pacific Coconut Community (APCC, 2003) and does not differ strikingly from each other. Subsequently, samples of VCO and LD were mixed in different concentration (v/v). Each sample admixtures were subjected to analysis of fast GC, FTIR and DSC. Some chemical analyses were performed such as iodine value (IV) and peroxide value (PV). In addition, fatty acid (FA) and triacylglycerol (TAG) analyses were also conducted using gas chromatography - flame ionization detector (GC-FID) and high performance liquid chromatography (HPLC), respectively, as the control experiments. Simple linear regression on fast GC data demonstrated that three peaks on the fast GC chromatogram were found to fit the second order polynomial curve with R2 of 0.8121, 0.8349 and 0.9344, respectively. Partial least square (PLS) from FTIR spectroscopy was able to predict LD adulteration in VCO with the equation y = 0.999x + 0.006. Meanwhile, DSC showed that Te A (endset peak A) in the endothermic curve and Tr D (temperature range for peak D) in the exothermic curve were found to have good predictor ability in determining percentage LD adulteration in VCO with the equation from step 2 of stepwise multiple linear regression (SMLR); % LD adulteration = 293.1 – 11.36 (Te A) – 2.17 (Tr D) and R2 adjusted of 95.82. To conclude, all three techniques were able to detect LD in VCO with ease and without the use of chemicals.